2013
DOI: 10.1007/s00198-013-2343-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in bone mineral density in men starting androgen deprivation therapy and the protective role of vitamin D

Abstract: Loss of BMD associated with ADT is greatest at the lumbar spine and in the first year. Vitamin D but not calcium may be protective particularly in the first year of ADT use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 33 publications
2
34
0
5
Order By: Relevance
“…(61) Ensuring that patients maintain adequate intakes of calcium and vitamin D also should be added to any comprehensive skeletal health program, although calcium and vitamin D by themselves are insufficient to limit ADT-associated bone loss. (62, 63)…”
Section: Prostate Cancermentioning
confidence: 99%
“…(61) Ensuring that patients maintain adequate intakes of calcium and vitamin D also should be added to any comprehensive skeletal health program, although calcium and vitamin D by themselves are insufficient to limit ADT-associated bone loss. (62, 63)…”
Section: Prostate Cancermentioning
confidence: 99%
“…Some studies showed a greater bone loss in the first 6 to 12 months of ADT use, and decline in bone density was much less prominent beyond the first year. 2,9ā€“11 In contrast, a large longitudinal study of 618 men with newly diagnosed advanced PCa showed that those with normal BMD (n = 124) or osteopenia (n = 241) at baseline had declining BMD for up to 7 years with GnRH agonist treatment, even though the latter received daily vitamin D (400 IU) and calcium (500 mg) supplements. 12 Thus, this indicates that the commonly prescribed vitamin D and calcium doses seem to be insufficient to prevent ADT-induced bone loss.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, in a prospective longitudinal study, Alibhai et al88 examined the long-term effects of calcium and vitamin D supplementation in 160 prostate cancer patients (mean age, 69 years), with and without ADT. Vitamin D, but not calcium, was shown to provide some protection from bone density loss, especially in the first year of ADT.…”
Section: Effect Of Nutrition and Dietary Supplements On The Complicatmentioning
confidence: 99%